Differences in patient-reported outcomes between medial opening-wedge high tibial osteotomy and total knee arthroplasty. (8th January 2020) - Matsumoto, Kazu; Ogawa, Hiroyasu; Yoshioka, Hiroki; Akiyama, Haruhiko
Purpose: To compare patient subjective satisfaction between medial opening-wedge high tibial osteotomy (HTO) and total knee arthroplasty (TKA). Methods: This study enrolled 110 knees, including comprising 49 knees in the HTO group, and 61 knees in the TKA group. We assessed the overall satisfaction using a three-point questionnaire. The satisfaction questionnaire included three questions: (1) How satisfied are you with the results of your knee surgery? (2) How satisfied are you with your most recent knee surgery for reducing your pain? and (3) How satisfied are you with your most recent knee surgery for improving your ability to perform functions? Furthermore, we assessed knee pain and function by using the Knee Society Function Score (KSS) and Knee Injury and Osteoarthritis Outcome Score (KOOS) systems. Results: Overall, 93.8% of patients from the HTO group and 95.1% from the TKA group indicated subjective satisfaction (very satisfied and satisfied) with their surgeries. For pain relief, the HTO group showed significantly better outcomes for overall satisfaction ( p = 0.04 in walking on a flat surface and p = 0.02 in going upstairs or downstairs). For restored function, the HTO group scored significantly better on ascending stairs than the TKA group ( p = 0.007). Functional outcomes using the KSS scoring system did not show significant differences between the two groups. The KOOS pain score was significantly higher in the TKA group (89.9 ± 6.4) than in the HTO group (80.3 ± 12.5). Conclusion: HTO and TKA have comparable outcomes with respect to overall patient satisfaction. Level of evidence: Level III, therapeutic case series.